Potestas Gladii in Jesus’ Trial - Kacian, Adrian (Communications - Scientific letters of the University of Zilina, 2014)
The question of potestas gladii in Jesus’ trial, i.e., who had the legal authority to put him to death has been for a long time one of the puzzles of the New Testament scholarship. The present article resolves the question with a balanced view that even if the ultimate potestas gladii belonged to the Roman procurator, the Jewish Sanhedrin possessed the right to condemn and execute Jesus to death on charges of the Temple offences and blasphemous utterances. However, Jesus´ activity encompassed more than just a religious threat. The Jewish representatives feared also a public tumult and uprising if they had tried to put Jesus to death by themselves. They also did not want to be publicly blamed by the masses for killing a prophet type of a person and thereby adding to their negative public reputation. Therefore they handed Jesus to Pilate even though they could execute him by themselves on the basis of blasphemy.